The Impact of Cognitive and Metacognitive Reading Strategies on EFL Students’ Reading Comprehension - Husna, Zumala; Wahyuni, Sri; Rukmini, Dwi; Wulandari, Rini Susanti (Universitas Negeri Semarang, 2025)
Academic success among EFL learners is closely linked to their foundational skills in reading comprehension. However, many students continue to struggle with understanding English texts within a limited timeframe. This difficulty stems from the fundamental purpose of reading: to comprehend written content in order to follow specific instructions. Since cognitive and metacognitive strategies are interrelated where metacognitive strategies oversee and regulate cognitive processes, their combined use is considered effective in enhancing reading comprehension skills. This study aims to investigate the extent to which cognitive and metacognitive reading strategies simultaneously impact EFL students' reading comprehension using mixed methods (quantitative-qualitative) of one-group pre-experimental design. Data were obtained through English literacy pre-test and post-tests, questionnaires, and classroom observation. The treatments were cognitive and metacognitive reading strategies taught by two expert teachers to 60 EFL students. Quantitative data were analyzed using descriptive statistics to investigate EFL students' reading comprehension and their reading strategy awareness before and after treatment. Inferential statistics using paired sample t-tests revealed a significant difference between EFL students’ reading comprehension before and after treatment (p-value<0.05). Analysis of multiple linear regression also revealed a significant impact of cognitive and metacognitive reading strategies on EFL students’ reading comprehension simultaneously (p-value<0.05 and FComputed>FTable) with an impact of 43.8% (moderate). Qualitative data analyzed descriptively revealed that almost all EFL students showed positive attitudes during the treatment given. This study is expected to present significant contributions for teachers to implement various cognitive and metacognitive reading strategies in their reading classes to enhance EFL students’ reading comprehension and assist them in overcoming the difficulties they face during the reading process.